Monetary policy divergence and net capital flows: Accounting for endogenous policy responses. (June 2019) - Scott Davis, J.; Zlate, Andrei
Highlights: We estimate the effect of foreign monetary shocks on capital flows in a panel SVAR. Domestic policy rates respond endogenously in line with the trilemma framework. We compute counterfactuals that abstract from the domestic policy response. The domestic response mitigates up to one third of net capital outflows. Abstract: This paper measures the effect of monetary tightening in key advanced economies on net capital flows around the world. Measuring this effect is complicated by the fact that the domestic monetary policies of affected economies respond endogenously to the foreign tightening shock. Using a structural VAR framework with quarterly panel data we estimate the impulse responses of domestic policy variables and net capital flows to a foreign monetary tightening shock. We find that the endogenous response of domestic monetary policy depends on each economy's capital account openness and exchange rate regime. We use a method to compute counterfactual impulse responses for net capital outflows under the assumption that the domestic policy rate does not respond to foreign monetary tightening. Our results suggests that failing to account for the endogenous response of domestic monetary policy biases down the estimated elasticity of net capital flows to foreign interest rates by as much as one-third for countries with open capital accounts.